An alternative strategy for cloning minor permeases in Aspergillus nidulans - L Harispe; P Tucci; C Portela; L Gorfinkiel (Fungal Genetics Reports, 2000)
The uapC gene was cloned by complementation of the cryosensitive phenotype of uapA mutants following the "instant gene bank" method. The analysis of the transformants is presented and a strategy to clone other transport related genes is proposed.